Phase 3 Study of Fezolinetant for Treatment of Moderate-to-Severe Vasomotor Symptoms Associated With Menopause [A132]. (May 2022) - Lederman, Samuel; Shapiro CM, Marla; Stute, Petra; Lee, Misun; Wang, Xuegong; Neal-Perry, Genevieve
Abstract : INTRODUCTION: SKYLIGHT 1 was conducted to evaluate the efficacy and safety of the novel non-hormonal treatment, fezolinetant, versus placebo in women with moderate-to-severe vasomotor symptoms (VMS) associated with menopause. METHODS: This phase 3, institutional review board approved, double-blind trial (NCT04003155) randomized women aged 40–65 years with moderate-to-severe VMS (≥7 hot flashes/day) to once-daily placebo, fezolinetant 30 mg, or fezolinetant 45 mg. Co-primary efficacy endpoints were mean change from baseline to week 4 and 12 in frequency and severity of moderate-to-severe VMS. Treatment-emergent adverse events (TEAEs) were assessed. RESULTS: Overall, 527 women were randomized; 522 took ≥1 dose (placebo n=175, fezolinetant 30 mg n=173, fezolinetant 45 mg n=174). Both fezolinetant doses were shown to statistically reduce VMS frequency and severity at both timepoints. For VMS frequency, least squares mean (standard error) reductions versus placebo at week 4 were –1.87 (0.42), P <.001 for fezolinetant 30 mg and –2.07 (0.42), P <.001 for 45 mg. At week 12, these values were –2.39 (0.44), P <.001 for 30 mg and –2.55 (0.43), P <.001 for 45 mg. For VMS severity at week 4, reductions were –0.15 (0.06), P =.012 for 30 mg and –0.19 (0.06), P =.002 for 45 mg; at week 12, reductions were –0.24 (0.08), P =.002 for 30 mg and –0.20 (0.08), P =.007 for 45 mg. TEAEs were reported by 37.4% (fezolinetant 30 mg), 43.4% (fezolinetant 45 mg), and 44.6% (placebo) of women. Headache was the most common TEAE: 5.2% (30 mg), 6.4% (45 mg), and 7.4% (placebo). CONCLUSION: Fezolinetant 30 mg and 45 mg were efficacious for the treatment of moderate-to-severe VMS associated with menopause. No safety signals of concern were apparent for either fezolinetant dose.